The X‐ray Correlation Spectroscopy instrument at the Linac Coherent Light Source. (13th April 2015) - Alonso‐Mori, Roberto; Caronna, Chiara; Chollet, Matthieu; Curtis, Robin; Damiani, Daniel S.; Defever, Jim; Feng, Yiping; Flath, Daniel L.; Glownia, James M.; Lee, Sooheyong; Lemke, Henrik T.; Nelson, Silke; et al.
<x xml:space="preserve">Abstract</x> The X‐ray Correlation Spectroscopy instrument is dedicated to the study of dynamics in condensed matter systems using the unique coherence properties of free‐electron lasers. It covers a photon energy range of 4–25 keV. The intrinsic temporal characteristics of the Linac Coherent Light Source, in particular the 120 Hz repetition rate, allow for the investigation of slow dynamics (milliseconds) by means of X‐ray photon correlation spectroscopy. Double‐pulse schemes could probe dynamics on the picosecond timescale. A description of the instrument capabilities and recent achievements is presented.